Review of Islamic Criminal Law on Criminal Sanctions for Persecution of Jumping Bastards in Belawan (Study Decision Number: 559/Pid.B/2022/Pn.Mdn.) - Hotma Ringan Limbong; Sukiati (Journal Equity of Law and Governance, 2024)
This study examines how judges determine criminal sanctions for perpetrators involved in the persecution of jumping squirrels under Islamic Criminal Law, focusing on Case Decision Number 559/Pid.B/2022/PN. Mdn. Using a normative legal research method, this literature-based analysis scrutinizes primary and secondary legal materials through a case and analytical approach. The study reveals that the judge classified the perpetrator's actions as 'persecution that resulted in death,' leading to a 5-year prison sentence, which was reduced due to the perpetrator's polite behavior and remorse. According to Article 351 Paragraph (3) of the Criminal Code, the standard penalty for persecution causing death is 7 years in prison. The judge's decision deviates from this guideline, reflecting a more lenient approach possibly influenced by the perpetrator’s conduct and regret. Under Islamic Law, such acts fall under 'murder by mistake,' where the perpetrator, lacking intent to kill, causes death through negligence. In Islamic Criminal Law, this would typically warrant diat (compensation), not ta’zir (discretionary punishment). However, since Indonesian law does not fully adhere to Islamic principles, the ta’zir punishment is deemed appropriate within the Indonesian legal context. This research contributes to legal development in Indonesia and serves as a reference for future studies on similar themes, advocating for better alignment and understanding between Islamic and national legal practices.